Modulation and optimization of terahertz absorption in micro-cavity quantum well structures by graphene grating. (21st January 2022) - Li, Zhiguo; Zhao, Qiang; Chen, Pingping; Wang, Jiqing
Abstract: Metal–insulator–metal-based plasmonic microcavities have attracted widespread interest due to their ability to manipulate and concentrate photons on the sub-wavelength scale. However, noble metals suffer from large intrinsic loss and lack active tunability. Here, a micro-cavity structure of a quantum well sandwiched between a periodic top contact of graphene grating and a bottom contact of graphene is proposed. Graphene plasmons provide a suitable alternative for metal plasmons and have the advantage of being highly tunable by electrostatic gating. The effect of changes in both the physical graphene and the device's structural parameters on optimized absorption performance is systematically analyzed through the calculation of reflectivity curves of incident light. Our results indicate that the intersubband absorption of the device can be improved by adjusting the parameters of both the graphene material and the device structure. Furthermore, the cavity resonant mode excited by surface plasmon polaritons can be tuned to the response frequency of the quantum well under optimized parameters. Intersubband absorption is almost 1.5 times higher than that of a micro-cavity structure that uses metal grating.